Potential-induced degradation in photovoltaic modules: a critical review. Issue 1 (8th December 2016) - Luo, Wei; Khoo, Yong Sheng; Hacke, Peter; Naumann, Volker; Lausch, Dominik; Harvey, Steven P.; Singh, Jai Prakash; Chai, Jing; Wang, Yan; Aberle, Armin G.; Ramakrishna, Seeram
Abstract : This paper presents a critical review on potential-induced degradation (PID) in photovoltaic modules to illustrate the current research status and potential research paths to address PID-related issues. Abstract : Potential-induced degradation (PID) has received considerable attention in recent years due to its detrimental impact on photovoltaic (PV) module performance under field conditions. Both crystalline silicon (c-Si) and thin-film PV modules are susceptible to PID. While extensive studies have already been conducted in this area, the understanding of the PID phenomena is still incomplete and it remains a major problem in the PV industry. Herein, a critical review of the available literature is given to serve as a one-stop source for understanding the current status of PID research. This paper also aims to provide an overview of future research paths to address PID-related issues. This paper consists of three parts. In the first part, the modelling of leakage current paths in the module package is discussed. The PID mechanisms in both c-Si and thin-film PV modules are also comprehensively reviewed. The second part summarizes various test methods to evaluate PV modules for PID. The last part focuses on studies related to PID in the omnipresent p-type c-Si PV modules. The dependence of temperature, humidity and voltage on the progression of PID is examined. Preventive measures against PID at the cell, module and system levels are illustrated. Moreover, PID recovery in standard p-type c-Si PV modules is also studied. Most of the findings from p-type c-Si PV modules are also applicable to other PV module technologies.